Effect of Fiber Type, Water Content, and Velocity on Wetness Perception by the Volar Forearm Test: Stimulus Intensity Test. (September 2019) - Zhang, Zhaohua; Tang, Xiangning; Wang, Yunyi; Li, Jun; Tian, Miao; Xiao, Ping
To investigate the effect of heat, moisture transfer, and mechanical tactile properties of fabrics on skin wetness perception when fabrics were in dynamic contact with skin at three velocities, nine knitted fabrics varying in fiber composition, thickness, and surface texture were evaluated by 20 participants using a wetness rating scale. The objective physical properties of the fabrics, namely, heat and moisture transfer and surface texture, and human physiological responses, namely, skin cooling rate and myoelectric signals, under various conditions were measured, and their correlations with the subjective wetness perception were studied. While the results indicated a significant influence of fabric type, water content, and velocity on skin wetness perception, no significant relation between electromyography and wetness perception was found. Fabrics with faster water spreading speeds and lower absorption rates were perceived as less wet, and the maximum transient thermal flow and skin cooling rate had a significant positive correlation with wetness perception. Furthermore, subjective wetness perception was predicted by the physical parameters of the fabric, that is, maximum transient thermal flow, water content, and friction coefficient, with an acceptable goodness of fit ( R 2  = 0.82, p  < .001).